Control del proceso de deshumidificación de muros con georradar. Un edificio patrimonial como caso de estudio. - Gea, Susana B.; Quinteros, R.; Nallim, L. (Revista ALCONPAT, 2014)
In historical buildings the harmful effects in masonry due to moisture are well known, as it affects ornamentation and the components of the masonry which is also the building’s structure. That is the case of the church Nuestra Señora de la Viña (Salta, Argenti na), a XIX cent. building which presented typical pathological symptoms caused by rising damp. An electro physical system was installed in order to dehumidificate the masonry and external surfaces were subsequently recovered. This high investment requires a periodical control of the system’s efficiency. This article presents the foundations of and the results obtained by using an impulse radar as a non-destructive resource to control the dehumidification system. Its main advantage is the early detecting of a failure in the system and so avoiding new pathological symptoms caused by rising damp.Keywords: Pathology masonry; moisture; radar.